Multiple systemic artery to pulmonary vessel fistulas (SAPVFs) completely resected by video-assisted thoracoscopic surgery: a case report - Kyoto Matsudo; Naoki Haratake; Yuki Ono; Mikihiro Kohno; Tomoyoshi Takenaka; Tomoharu Yoshizumi (Surgical Case Reports, 2022)
Abstract Background Systemic artery to pulmonary vessel fistula (SAPVF) is an uncommon abnormal vascular communication between systemic arteries and the lung parenchyma. It has been reported that the appropriate treatment for SAPVF is embolization or surgical resection. However, in patients such as ours, who have many aberrant vessels or multiple lesions, surgery should be considered as the first-choice treatment. Case presentation This case report describes multiple SAPVFs and huge bullae at the apex of the left lung in a 43-year-old man that were resected completely with the video-assisted thoracoscopic surgery (VATS). The patient had an uneventful postoperative recovery without any complications and was discharged 9 days postoperatively. He had heavy smoking history, and the giant bullae and the diffuse emphysematous change were found in the lung. Therefore, the chronic inflammation may have been present in the thoracic cavity, which caused multiple SAPVFs. Conclusions We describe the clinical course and management of the patient with multiple SAPVFs who had no obvious history of surgery, trauma, or various inflammatory or infection diseases. VATS should be the first-choice treatment in patients with many abnormal vessels or multiple lesions.